The Influence of Internal Control, Audit Committee, Whistleblowing System, and Moral Sensitivity on Fraud Prevention - Elvina Sephia Hardiyanti; Dirvi Surya Abbas (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The primary objective of this study is to evaluate how internal controls, audit committee efficiency, whistleblowing systems, and moral sensitivity influence efforts to minimize fraud in infrastructure corporations listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. Using a quantitative approach, this study tests the hypothesis regarding the positive and significant impact of each independent variable on fraud prevention. Secondary data sourced from companies’ annual reports were selected using purposive sampling. To test the relationships among variables, the researcher applied panel data regression with a fixed-effects model. The analysis results indicate that strengthening corporate governance and collective moral awareness collectively enhance the effectiveness of fraud prevention. These findings confirm that robust governance mechanisms are a crucial instrument in mitigating the risk of illegal activities within organizations. The implications of this research suggest that management should be more proactive in optimizing the role of the audit committee and fostering moral sensitivity as a long-term preventive strategy.